PENGGUNAAN METODE BRAIN GYM TERHADAP KEMAMPUAN MENYIMAK ANAK AUTIS - WIDAD, AINUL (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Scrutinizing skill was one of the aspects in speech. Scrutinizing skill with attention and comprehension was so important for the children’s development of speech skill because most of teaching-learning process in the school used oral language. Scrutinizing skill was experienced by the autism children with disturbance in receptive language skill and tended to stand out in using language for communicating to others. If the disturbance of scrutinizing to the autism children was not handled they would have experienced disturbance during learning Indonesian lesson. The purpose of this research was to observe the scrutinizing skill of autism children before and after giving intervention using Brain Gym method. This research used Single Subject Research (SSR) with A-B-A design. The time used was 32 times meeting i.e. 9 times meeting to baseline phase (A), 18 times meeting to baseline phase (B), 5 times meeting to baseline phase (A2). The techniques of data collection used were observation and documentation. The technique of data analysis used was visual analysis inside condition and among condition. The scrutinizing skill of autism children in SLB Al Falah Sembayat Manyar Gresik before giving intervention only 5 times emerged the ability in scrutinizing which included listening ability, understanding ability, and responding ability. However, after giving intervention in the form of giving Brain Gym method in learning, the trend experienced enhancement in steps i.e. 16-19 times emerged the scrutinizing ability of autism children which included listening, understanding, and responding to each meeting. The research result indicated that to baseline phase (A1) the average frequency appearance of tending behavior showed 6. Intervention phase (B) indicated 17. And to baseline repetition phase (A2) tended 12. The subject percentage to overlap data of intervention phase (B) to baseline (A) was 0% while the percentage to overlap data of intervention phase (B) to baseline repetition phase (A2) indicated 0%. It could be stated that the application of Brain Gym method could enhance scrutinizing ability to autism children in SLB Al Fatah Sembayat Manyar Gresik.   Keywords: Scrutinizing ability, Brain Gym